Cattle tick vaccine - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
An annual vaccine to control cattle ticks may soon replace the chore of regular dipping. In Australia researchers at the Commonwealth Scientific and Industrial Research Organization (CSIRO) and Biotechnology Australia Ltd found that if cattle were...